2022
DOI: 10.3389/fmed.2021.810940
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Pathogenic Missense Variant of WT1 Cosegregates With Proteinuria in a Six-Generation Chinese Family With IgA Nephropathy

Abstract: Immunoglobulin A (IgA) nephropathy (IgAN) is the most common type of primary glomerulonephritis worldwide. In addition to hematuria, proteinuria is observed in a considerable proportion of patients with IgAN and has proven to be a strong risk factor for disease progression. Although the exact pathogenesis of IgAN is still unclear, genetic factors are widely considered to play a role in its occurrence and development. Here, we investigated a large IgAN-associated pedigree of 47 members belonging to six generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…SLE is a chronic autoimmune disease that can damage several organs including kidneys. About one half of patients with SLE develop kidney disease which can lead to ESKD [92]. While light microscopy studies revealed a membranoproliferative pattern of glomerular injury with extensive subendothelial deposits, resulting in wire loop appearance, electron microscopy studies showed mesangial and subendothelial deposits of IgG and tubuloreticular aggregates [93].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…SLE is a chronic autoimmune disease that can damage several organs including kidneys. About one half of patients with SLE develop kidney disease which can lead to ESKD [92]. While light microscopy studies revealed a membranoproliferative pattern of glomerular injury with extensive subendothelial deposits, resulting in wire loop appearance, electron microscopy studies showed mesangial and subendothelial deposits of IgG and tubuloreticular aggregates [93].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Besides, many cases revealed various rare variants associated with IgAN. For example, a likely pathogenic variant of WT1 was found by WES to be co-segregated with proteinuria in a six-generation Chinese family with IgAN [ 10 ]. In this family, another WT1 variant was harbored by those patients whose phenotype was more severe.…”
Section: Discussionmentioning
confidence: 99%